Influence of stream connectance and network spatial position on fish assemblage structure in the Kansas River basin, USA - Thornbrugh, Darren Jay (Kansas State University, 2008)
Stream networks provide complex habitats for fish assemblages that can vary gradually along a gradient of stream size or abruptly at transition zones between large rivers and their tributaries. We evaluated the relative importance of these gradual and abrupt habitat transitions in regulating stream fish assemblages by quantifying roles of stream size and spatial position within a drainage network as a determinant of fish assemblage structure within the Kansas River basin, KS. We predicted fish assemblage structure to generally be dependent on stream size and that smaller streams would be influenced by their connectance to larger mainstem rivers. Fishes in the Kansas River basin varied along a gradient of stream size and longitude, and after controlling for these effects, there was evidence that connectivity to a larger river influenced species richness and assemblage structure. In 1st order streams there was an increase in species richness with increasing distance from a mainstem confluence and species composition in larger tributaries (i.e., 4th order streams) varied with proximity to the mainstem river. We also found an increase in species richness at sites located on smaller tributaries connected to a larger downstream mainstem. Species composition in 1st and 4th order streams also varied with connectance to the mainstem river. Within three intensively sampled tributaries, there was an abrupt change in fish fauna between the Kansas River and sample sites above the confluence, but only gradual change in assemblage structure within each tributary with a high degree of seasonal variation. In the first 20 stream km of these three mainstem tributaries adult fishes were more structured along a gradient away from the mainstem river than juveniles, potentially suggesting more generalized habitat needs of juvenile fishes. At the spatial and temporal scale of our analysis, it appeared the effects of large rivers on tributary streams were generally localized. However, the documented influence of spatial position suggests movements between habitats could regulate community level dynamics as well as individual species over longer temporal scales.
Keywords: fish; stream; connectance; assemblage; structure; network; Biology, Ecology (0329)